Den første ‘grænseredder’: Ejnar Vaaben og den berlinske linie - Lauridsen, John T. (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2015)
John T. Lauridsen: The first “border saver”. Ejnar Vaaben and the Berlin Line.   Ejnar Vaaben was a Danish Nazi at a relatively early point in time and established contacts with the prototype of the NSDAP (the National Socialist German Workers’ Party) and some of its leaders in Germany before Hitler took power in January 1933. These contacts were of such significance at the time, and later, that Vaaben attributed to himself the honour of having led the German Nazis to maintain the Danish-German border as it was. According to him, he also attempted to work for a change of the border in Denmark’s favour. The article examines the limited material on Vaaben’s presumed border-change activities and alleged close contact with, and influence on, the Nazi leaders, just as his later efforts during the German occupation are viewed in this light, since his memoirs, written later, are compared with material from the same period. The conclusion drawn is that this was a self-centred, self-aggrandising assessment on the part of Vaaben, masking the attempt of an insignificant political fantasist and traitor to earn a place in Danish history.